ANALISIS IMPLEMENTASI PENDIDIKAN UNTUK PEMBANGUNAN BERKELANJUTAN DAN CAPAIAN KEY COMPETENCES ESD SERTA KEDADARAN BERKELANJUTAN - Syahirah, St.; Diana Rochintaniawati; Eni Nuraeni; Mimin Nurjhani Kusumawati (LPPM Universitas Muhammadiyah Muara Bungo, 2025)
Education plays a strategic role in shaping cultural behavior and developing human resources. Integrating Education for Sustainable Development (ESD) into biology learning offers a promising strategy to enhance students’ sustainability awareness. This study aims to examine the achievement of key ESD competencies and identify students’ levels of sustainability awareness in the context of ESD-based biology instruction. A qualitative descriptive approach was employed in a public senior high school in Bandung during the second semester of the 2023/2024 academic year. Research participants included a biology teacher and eleventh-grade students. Data were collected through in-depth interviews, questionnaires, and document analysis of teaching modules and student worksheets. Thematic analysis was used to identify ESD-related competencies and expressions of sustainability awareness. The results indicate that integrating Problem-Based Learning (PBL) into biology lessons supports the development of ESD competencies, particularly systems thinking and self-reflection. However, the assessments embedded in the worksheets remain limited to lower-order cognitive levels and do not adequately stimulate higher-order thinking skills (HOTS). Students’ sustainability awareness was most prominent in environmental aspects, followed by social dimensions, while economic awareness remained underdeveloped. These findings highlight the need to strengthen ESD-based content and assessment strategies that encourage students’ active engagement with real-world sustainability issues.